A Comparison of the Hard-Switching Performance of 650 V Power Transistors With Calorimetric Verification - Daniel J. Rogers; Jack Bruford; Aleksandar Ristic-Smith; Kawsar Ali; Patrick Palmer; Edward Shelton (IEEE Open Journal of Power Electronics, 2023)
We compare the switching losses of four equivalent silicon and wide-bandgap 650 V power transistors operated in a hard-switched half-bridge configuration, switching 400 V at 40 A. Each transistor is mounted on an identical PCB and driven by a gate drive circuit matched to its requirements. Switching speed is maximised by a PCB design featuring very low parasitic inductance and the use of zero external gate resistance (where possible). Switching losses are measured electrically using a Double Pulse Test (DPT) method. However, high-bandwidth electrical measurements are prone to error and so we assess the gain accuracy, offset accuracy, and the bandwidth requirements of the DPT measurements, and then verify the DPT results by calorimetry. The electrical and calorimetric measurements are shown to agree to within 5%. Comprehensive plots of gate-source voltage, drain-source voltage, and source current are provided for all transistors over a junction temperature range of 50–150°C. The ratio of the total half-bridge switching losses is 1:3.2:14:31 for the GaN HEMT, SiC MOSFET, Si IGBT, and Si superjunction MOSFET, respectively.